Contribuição ao estudo da reforma a vapor do glicerol em catalisadores Pt/c: efeito do tamanho da partícula de Pt e do Ph da solução de alimentação - Martins, Douglas Ferreira (2009)
With the increase in biodiesel production, it is expected that large quantities of glycerol are available on the market at reasonable prices. It is moreover relevant and promising to search for processes that lead to the glycerol value-added products. Furthermore, glycerol is considered one of the 12 key molecules most promising for use in future bio-refineries. In this sense, this dissertation aimed to contribute to a better understanding of the reaction of steam reforming of glycerol using platinum catalysts supported on carbon. This system has been used lately as an excellent provider of synthesis gas at low temperatures, which, integrated with other catalytic systems, can produce hydrogen (with WGS) and fuel (to SFT) in a single reactor. In this thesis, we evaluated the effect of particle size of platinum and the pH of the feed solution in the reaction of steam reforming of glycerol. For this study, we used commercial catalysts BASF (E-Tek) supported on carbon (Vulcan X-72), containing 5,0, 10,0 and 20,0% by weight of Pt catalysts containing 0,5, 1,0, 2,0 and 3,0% by weight of Pt, supported the same type of carbon, but prepared in the laboratory, via dry impregnation of aqueous solution of hexacloroplatinium followed by drying at 120 ° C for 12 hours. The prepared and commercial catalysts were characterized by the technique of volumetric chemisorption of CO to obtain the number of active sites available, dispersion and average size of the metal particle. For this characterization, the catalysts were activated using the same procedure that is done before the catalytic tests, or raising the temperature to 1°C/min to 350°C under a flow of ultra pure H2, staying in for 2 hours. These catalysts were evaluated for the reforming reactions of glycerol gas at atmospheric pressure, varying the reaction temperature (275-350 °C), the mean residence time (WHSV = 33, 66, 99 min-1) and pH of the aqueous solution glycerol (30% by weight) of food. The pH was modified, reaching values of 3 and 10, adding acid (HNO3) or base (NH4OH) compounds, respectively, in aqueous, near neutral (pH = 6,5) of 30% by weight of glycerol. The results showed that the reaction of hydrogenolysis of glycerol is sensitive to the structure, both for activity and for selectivity. In other words, the reaction rate and selectivity to products of degradation / decomposition (breaks C C bonds), mainly synthesis gas, increased with the size of the metal particle. While, acetol, product formed by the breakup of the preferential binding C O (via dehydration) for C C, is preferentially formed when small particles are present. The catalytic tests for the change in pH of the solution proved to be more selective gas (CO) in basic medium. Alongside the formation of CO, we observed the production of acetol was favored in several situations: in flow (WHSV) high and / or conversions and low in acid, by adding inorganic acid. The lower the temperature of reaction, less carbon monoxide and more acetol are formed. This trend of decrease of CO selectivity was more marked in percentage terms for the reaction in acidic than basic. Furthermore, the increased selectivity to acetol is greater, in percentage terms in basic medium in relation to acid. With these results, a proposed reaction mechanism was presented.